EMF equation of Transformers:

A transformer is a static device which has two windings,, one is primary winding and other is secondary winding.When an alternating current is applied to primary an alternating flux is developed ,which links with secondary windings and an emf is induced in the secondary windings according to mutual induction.This magnitude of induced emf can be found using the below emf equation of transformer.  
emf equation of transformer
                    E.M.F equation of a transformer                       

Let  N1 = number of turns in primary windings
      
      N2  = number of turns in secondary windings 

      Î¦m= Maximum flux in core in webers
          = BA
       f = frequency of a.c. input in Hz

As shown in the above figure of EMF equation of transformer, flux increases from its zero value to maximum value Î¦m in one quarter of cycle i.e. 1/4f second .

    Average rate of change flux = Î¦m/(1/4f)

                                             = 4fΦm
Rate of change of flux per turn means induced e.m.f in volts.
             
                            Average e.m.f/turn = 4fΦmvolt 
If flux Î¦varies sinusoidally, then r.m.s value of induced e.m.f is obtained by multiplying the average value with form factor.

                        Form factor = r.m.s value/average value = 1.11

Now r.m.s value of induced e.m.f in whole of primary = (induced e.m.f/turn)x number of primary turns 

          E1 = 4.44fN1Φm
              
          E1 = 4.44fN1BA      

Similarly, r.m.s value of the  induced emf in secondary of transformer is 

          E2 = 4.44fN2BA             

It can be observed from above equations that 
              
          E1/N1 = E2/N2 = 4.44fΦm

This is the emf equation of transformer, which means that e.m.f/turn is the same in both the primary and secondary windings.

For an ideal transformer on no load, E1 = V1 and E2 = V2 .

where   V1 = supply voltage of the primary winding
             V2 = terminal voltage of secondary winding

Voltage Transformation Ratio(K):

From equations above we get 

                       E2/E1 = N2/N1 =k

the constant 'K' is called voltage transformation ratio .

1. If N2>N1 i.e. K>1, then transformer is called Step up transformer .

2. If N2<N1 i.e. K<1, then transformer is called Step down transformer .
Previous Post Next Post